Early Film Culture in Hong Kong, Taiwan, and Republican China Kaleidoscopic Histories - Yeh, Emilie Yueh-yu (University of Michigan Press, 2018)
This volume features new work on cinema in early twentieth-century Hong Kong, Taiwan, and Republican China. Looking beyond relatively well-studied cities like Shanghai, these essays foreground cinema's relationship with imperialism and colonialism and emphasize the rapid development of cinema as a sociocultural institution. These essays examine where films were screened; how cinema-going as a social activity adapted from and integrated with existing social norms and practices; the extent to which Cantonese opera and other regional performance traditions were models for the development of cinematic conventions; the role foreign films played in the development of cinema as an industry in the Republican era; and much more.